Solar Energy Conversion: Multifunctional Solar Waterways: Plasma‐Enabled Self‐Cleaning Nanoarchitectures for Energy‐Efficient Desalination (Adv. Energy Mater. 30/2019). Issue 30 (14th August 2019) - Wu, Shenghao; Xiong, Guoping; Yang, Huachao; Gong, Biyao; Tian, Yikuan; Xu, Chenxuan; Wang, Yan; Fisher, Timothy; Yan, Jianhua; Cen, Kefa; Luo, Tengfei; Tu, Xin; et al.
Abstract : In article number1901286, Zheng Bo and co‐workers produce on‐surface waterways by integrating hydrophilic on‐surface light‐absorbers and hydrophobic internal thermal‐insulators into an all‐carbon nanoarchitecture with self‐cleaning and anti‐salt‐fouling behavior. The heat conduction loss for solar desalination is thus suppressed, achieving high solar‐vapor efficiency, high daily clean water yield, and long‐term stability.